Defining the defence industry using an ecological system and the application of ecological taxonomy - Fisher, Richard (Cranfield University, 2017)
This research examines the creation of the ecosystem where the defence industry is described using an ecological taxonomy and the development of the theory supporting classification of defence organisations within that taxonomy. Using recognised terminology, comparisons are made between defence organisations and organisms, associations and partnerships with populations and species, leading up to industry sectors and ecosystems and multiple sectors and biomes. The value of this approach is the ability to identify susceptibilities, resilience issues and the scope and interdependencies of defence. It enables those involved to reflect upon the organic natures of a complex system of systems. This work has already been applied to improving the visibility and transparency of the issues facing UK-based small-to-medium enterprises and the approach to exporting defence products.